Impact of systemic treatment of psoriasis on inflammatory parameters and markers of comorbidities and cardiovascular risk: results of a prospective longitudinal observational study. (24th August 2013) - Montaudié, H.; Albert‐Sabonnadière, C.; Acquacalda, E.; Fontas, E.; Danré, A.; Roux, C.; Ortonne, J.P.; Lacour, J.P.; Euller‐Ziegler, L.; Passeron, T.
Abstract Background Several markers of comorbidities and cardiovascular (CV) risk are disturbed in moderate to severe psoriasis (PsO). The effect of systemic treatments of psoriasis on these markers remains poorly understood. Objectives To study the frequency of disturbance of inflammatory parameters and markers of comorbidities and CV risk associated with moderate to severe PsO and psoriatic arthritis (PsA), and to assess their evolution under systemic treatments. Methods Monocentric prospective study on patients with PsO and PsA starting a systemic treatment for their psoriasis. The following markers were evaluated at baseline (M0), 3 months (M3) and 6 months (M6); weight, fasting blood glucose, blood pressure, uric acid, hepatic steatosis, smoking, lipid, metabolic and inflammatory parameters. Results Forty‐three patients, 31 PsO and 12 PsA, were included. Forty completed the study. Response to treatment was good, with 71% of the population obtaining a Psoriasis Area and Severity Index (PASI) of 75. All patients had at least one comorbidity, and 45% had two or more. A statistically significant decrease was observed only for inflammatory parameters (C‐reactive protein [CRP], P = 0.004) and erythrocyte sedimentation rate (ESR, P = 0.002). We did not observe any correlation between the PASI and CRP (correlation coefficient 0.128, P = 0.438) or ESR (correlation coefficient 0.294, P = 0.069) for responding patients. Conclusions We observed a high frequency of disturbance of inflammatory parameters and markers of comorbidities and CV risk in a population with moderate to severe PsO and PsA, most of which were not detected before. A significant decrease in inflammatory parameters was noted after the introduction of systemic therapy, while other parameters remained unaffected by the treatment, except the weight that increased under biologics therapies.